Implementation Of The Angkle Foot Orthosis And Prosthetic Csr Program By Pt Pelindo Solusi Logistik - Amelia Nova Lestari; Samsul Ode (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
PT. Pelindo Solusi Logistik is one of the subsidiaries of the Indonesian state-owned port company, PT. Pelabuhan Indonesia (Persero). One of the CSR programs of PT. Pelindo Solusi Logistik that interest the researcher is the provision of Ankle Foot Orthosis (AFO) and Prosthetic Legs to people with disabilities. The purpose of this research is to determine the implementation of the CSR program carried out by PT. Pelindo Solusi Logistik. The method used is descriptive qualitative method using indicators from Grindle's theory (1980). The results of this research indicate that the implementation of the CSR program by the state-owned enterprises has been carried out well. Using Grindle's theory (1980) approach, the first indicator is the presence of clear and directed policy goals or objectives. PT. Pelindo Solusi Logistik supports the CSR program of providing free Ankle Foot Orthosis (AFO) and Prosthetic Legs to assist the government's program in the functional rehabilitation of people with disabilities. The second indicator is the presence of activities or efforts to achieve the goals. The provision of assistance is channeled through the Yayasan Peduli Tuna Daksa (Care Foundation for the Disabled) under the theme "New Steps, New Spirit." The third indicator is the output or results of the activities. People with disabilities benefit from the provision of free Ankle Foot Orthosis (AFO) and Prosthetic Legs, and PT. Pelindo Solusi Logistik achieves a positive image among the community as an output.